Tribute to Luis Felipe de las Casas Grieve - Cuentas Vargas, Sergio (2024)
On the occasion of the commemoration of the 40th anniversary of the creation of the Faculty of Economic Engineering, Statistics and Social Sciences at the National University of Engineering, a tribute was paid to Luis Felipe de las Casas Grieve, who was the Founding Master of the specialty of Economic Engineering at UNI and in Peru.